An Overview on Solar Photovoltaic and Roof Top Application of IT (International Journal of Innovative Research in Computer Science & Technology, 2020)
Since first oil embargo in 1973, the terms  "energy crisis" and "energy security" have been constantly  in the headlines. Concerns about environmental effects  from fossil fuel-based power production have been a  source of worry for a long time. Despite efforts to  encourage renewable energy sources, fossil fuel-based  electricity production continue to control the market. Since  coal-fired energy is much more affordable and available to  consumers than any other fossil fuel, new nuclear power  plants are being built to run at "supercritical" and "ultra supercritical" temperatures and pressures, increasing  power generation efficiencies from 30percent to 50percent  or more. These new coal technologies promote the use of  coal forever for power generation and other purposes,  making it more difficult for renewable energy becoming a  significant component of the energy mix. To meet growing  energy demands and also as part of the National Action  Plan for Climate Change, a shift from conventional to non conventional energy sources is required (NAPCC). Solar  radiation, on the other hand, is the most abundant as well  as direct source of perpetual energy. This article focuses  on photovoltaic solar technology for power generation and  an assessment of its roof-top use.
Keywords: Application; Energy; Photovoltaic cells; Renewable source; Solar Energy